Antacid therapy and disease progression in patients with idiopathic pulmonary fibrosis (IPF) under pirfenidone treatment - Kreuter, Michael (Thorax, 2016)
Introduction On the basis of retrospective and post-hoc analyses the current IPF guideline suggests the use of anti-acid therapy (AAT, i.e., proton pump inhibitors and H2-blockers) as a treatment option in patients with IPF. While recent post-hoc analyses do not support a protective effect of AAT on IPF progression in patients receiving placebo, the impact of AAT on disease progression in patients treated with pirfenidone is unknown. Methods Patients with IPF randomised to pirfenidone in 3 trials (CAPACITY studies 004 and 006, and ASCEND) were included. Changes in pulmonary function, exercise tolerance, survival, hospitalizations, and adverse events (AEs) over 52 weeks were analysed for all subjects, based on AAT status at baseline, by bivariate and multivariate analyses. Disease progression was defined as an absolute decrease of forced vital capacity (FVC) ≥10% predicted, a decrease of ≥50 m in the 6-minute walk distance (6MWD) or death. Results Of 623 patients, 44% received AAT. Patient characteristics were comparable between groups with the exception of gastrointestinal (GI) comorbidities. In bivariate analyses, there were no significant differences at 52 weeks in disease progression (AAT vs non-AAT: 24.9% vs 30.6%; P = 0.12), all-cause or IPF-related mortality (2.9% vs 4.0%; P = 0.47 and 1.1% vs 2.0%; P = 0.37, respectively), all-cause hospitalisation (16.1% vs. 18.3%, P = 0.48) or observed mean FVC decline (−2.7% vs −3.1%, P = 0.44). Relative but not absolute FVC decline ≥10% was slightly in favour of AAT (15% vs 22%; P = 0.03). In multivariate analyses, hazard ratios across study outcomes ranged from 0.3-0.9 for AAT (vs. non-AAT), although differences were not statistically significant (including relative FVC decline ≥10%). AEs were generally similar between groups; however, severe GI AEs (3.7% vs. 0.9%, P = 0.015) and severe pulmonary infections (3.7% vs. 1.1%, P = 0.035) were more frequent in AAT users. Conclusion In this post-hoc analysis of three randomized-controlled trials, there was no clear evidence of benefit of the combination of AAT and pirfenidone compared to pirfenidone alone. However, AAT use appeared to increase the risk of severe GI and infectious AEs. AAT should be prospectively assessed in a randomised controlled trial before being considered as a specific treatment for IPF.
Gesehen am 11.09.2017